Resveratrol Improves Growth Performance, Intestinal Morphology, and Microbiota Composition and Metabolism in Mice - Zhuang, Yu; Huang, Huijun; Liu, Shuang; Liu, Feng; Tu, Qiang; Yin, Yulong; He, Shanping (Frontiers in Microbiology, 2021)
Background: Resveratrol (RSV) plays a vital role in alleviating various stresses and improving intestinal health. The aim of current study was conducted to explore whether RSV alleviates weanling stress through improve gut health in a weaning mouse model. Forty 21-day-old weaned mice were assigned to a control group without RSV and three treatments with 10 mg/kg/day, 20 mg/kg/day, and 50 mg/kg/day RSV for 28 days. Results: The results showed that mice supplemental with 20 mg/kg/day RSV improved total body weight, intestinal morphology (i.e. villus length, villus to crypt ratio) and intestinal barrier protein (i.e. claudin-1, occludin), but had little effect on the food intake, crypt depth, serum free amino acids. Mice supplemental with RSV had lower mRNA expression of genes related to inflammatory cytokines (i.e. IL-6 and IL1-β), but mRNA expression of genes related host defense peptide (i.e Defa3, Defa5, Defa20, and Lyz) and short-chain fatty acids (SCFAs) production (i.e. propionic acid, isobutyric acid, butyric acid, and isovaleric acid). In addition, 16S rRNA sequencing suggested that RSV supplementation increased the richness indices of intestinal microbiota (Chao, ACE), and shaped the composition of intestinal microbiota (e.g. increased β-diversity of intestinal microbiota community). Meanwhile, RSV supplementation increased genes of Butyricicoccus, Ruminococcus_1 and Roseburia which were producer of SCFAs. Furthermore, RSV supplementation also significantly influenced the metabolism of intestinal microbiota, such as amino acids metabolism, lipid metabolism and defense mechanisms. Conclusion: RSV can improve growth performance and intestinal morphology in weanling mice, possibly through improving gut immune response, and microbiota function.